DEVICE FOR DETECTING A MEDICAL CONDITION OF A SUBJECT - CAI PEIHUA (2022)
The present invention relates to a device (10) for detecting a medical condition of a subject from menstrual blood, the menstrual blood being collected from the subject, the device (10) comprising a sampling member (12) comprising one or more polymeric materials, the sampling member (12) being disposed in contact with the menstrual blood, the sampling member (12) collects constituent biomolecules of the menstrual blood at the polymeric material; and a positioning member (14), the positioning member (14) comprising an absorbent material, the positioning member (14) being configured to support the sampling member (12); wherein the positioning member (14) is releasably attached to a hygiene product wearable by the subject. 本发明涉及一种用于从经血中检测对象的医疗状况的装置(10)，所述经血从所述对象收集，所述装置(10)包括采样构件(12)，所述采样构件(12)包括一种或多种聚合物材料，当布置成与所述经血接触时，所述采样构件(12)在所述聚合物材料处收集所述经血的组成生物分子；以及定位构件(14)，所述定位构件(14)包括吸收材料，所述定位构件(14)被配置为支撑所述采样构件(12)；其中，所述定位构件(14)可释放地附接到所述对象可穿戴的卫生产品。